Surface engineering of Sio2-Zro2 films for augmenting power conversion efficiency performance of silicon solar cells - Amira Ben Gouider Trabelsi; Gobinath Velu Kaliyannan; Raja Gunasekaran; Rajasekar Rathanasamy; Sathish Kumar Palaniappan; Fatemah H. Alkallas; W.B. Elsharkawy; Ayman M. Mostafa (Journal of Materials Research and Technology, 2024)
Improving solar cell performance hinges significantly on the application of anti-reflective surface coatings. A wide variety of coating techniques, including blade coating, spin coating, dip coating, and others were employed. The present research investigation employed various coating materials, namely SiO2 (Silicon dioxide), ZrO2 (Zirconium dioxide), and SiO2–ZrO2 blends, to apply a protective layer onto polycrystalline silicon solar cells using the sputter coating process. The efficiency of these solar cells with multilayer coating was assessed through diverse characterization methods. The uniform thin films were obtained using a 45-min coating process using an input voltage source of 17 kV, which was confirmed through analyses conducted using FESEM and AFM techniques. The UV–Vis spectroscopy and current-voltage source metre were employed to examine the light absorption and transmittance of bare and coated silicon solar cells. When compared to alternative solar cells, the solar cell coated with a combination of SiO2 and ZrO2 demonstrated uniform deposition and a low light reflectance of only 6 %. SiO2–ZrO2 gains a highest power conversion efficiency (PCE) of 17.6 % under controlled light source. This superior performance was due to the increase in photon transmittance in to the depletion region. Furthermore, the electrical resistivity of the SiO2–ZrO2 blend coated solar cell was measured using the four-probe method was found to be 2.89 × 10−3 Ω-cm, which was lower than that of other solar cells. From the experimental results, it was clear that SiO2 - ZrO2 blend-coated solar cells outperformed both other coated and uncoated solar cells. Consequently, SiO2–ZrO2 blends emerged as superior anti-reflective materials for achieving peak performance.